SELEKSI BERKORELASI PADA PERTUMBUHAN PRASAPIH DAN PASCASAPIH KAMBING PERANAKAN ETAWAH KELOMPOK TERNAK MARGARINI VI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN - Zacky Faisal Haq; Sulastri .; Idalina Harris (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2013)
Selection on growth pre weaning addition can improve the growth of livestock post weaningconcerned can boost growth. Post weaning growth due to selection on growth pre weaningexpressed as a correlated response to selection caused by a genetic correlation between the natureof the growth. The aim of this study to determine the genetic correlation between growth preweaning and post weaning Peranakan Etawah goats (PE) in the village Sungailangka, DistrictGedongtataan, Pesawaran District, Lampung Province. Research conducted the survey methodsand explore secondary data is a record growth of 40 breeding goats and 40 tai female kids,regardless of the delivery period, the Group Livestock Margarini VI. Data recording are used tocalculate the corrected weaning weight and the entire year. Parent group then used to calculategrowth pre weaning and post weaning parent. Records used to calculate kidd and the entire yearcorrected weaning weight, then used to calculate growth pre weaning and post weaning kids. Datagrowth pre weanig and post weaning parent and kidds is used to estimate the heritability of growthpre and post weaning. Genetic correlations between growth pre and post weaning analyzed withregression methods to parent kidds. Results of this study showed that the estimated geneticcorrelation between growth pre and post weaning of 0.9968 ± 0.0002 thus included in the categoryof high positive.